Isolating the effects of equine hoof shape measurements on capsule strain with finite element analysis - McClinchey, H. L.; Thomason, J. J.; Jofriet, J. C. (Veterinary and Comparative Orthopaedics and Traumatology, 2003)
The shape of the equine hoof capsule affects how weightbearing forces are resisted by the capsule and are transmitted to deeper structures within the hoof. Our aim was to isolate the effects of several measurements describing hoof shape on strains and stresses in the hoof capsule. Multiple finite-element models are constructed with toe angles in the range 42° to 58°, heel angles from 34° to 50°, toe lengths of 8.5 to11.5 cm, and medial and lateral angles from 68° to 83°. Strain at the toe is inversely related to toe angle, and not strongly affected by heel angle; it increases with toe length distally on the toe, but decreases near the coronary border. Varying medial and lateral angles show that more upright walls have less strain at the quarters. This study demonstrates the effectiveness of finite element methods in complementing in vitro and in vivo studies of hoof mechanics.
Keywords: Finite-element; horse; hoof; shape; strain